British Language Policy in Colonial Sindh - Saqlain Shah; Kiran Fatima; Faryal Wadho (University of Chitral Journal of Linguistics and Literature, 2024)
This paper explores the language policy of the British government in colonial Sindh. The study relies on secondary data and follows the literature study framework to identify the explicit language policy and its implicit political goals. Also, it discusses the language policy of Sindh before the arrival of the British to build the context in which the British government started its rule and administration in Sindh. It is evident that after a series of battles and conflicts with the Talpurs of Sindh, British troops conquered Sindh in 1843 under Sir Charles Napier. Persian was the official language of Sindh before the arrival of the East India Company. However, the British chose to run the administration of Sindh in an indigenous language called Sindhi (also referred to as Scindee, Scinde, or Scindhee). For this purpose, they formulated a committee to devise a standard alphabet for the Sindhi language, and by 1853, a fifty-two-lettered 'Sindhized-Arabic' or 'Perso-Arabic-Sindhi' writing system of the Sindhi language was introduced. This newly codified version of the Sindhi language became the official language of Sindh under British rule. Civil servants in Sindh were required to learn Sindhi; books were printed in this language, and it was raised to the level of medium of instruction in the British educational system in Sindh.